2016
DOI: 10.1103/physrevd.94.123516
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological bounces and Lorentzian wormholes in Galileon theories with an extra scalar field

Abstract: We study whether it is possible to design a "classical" spatially flat bouncing cosmology or a static, spherically symmetric asymptotically flat Lorentzian wormhole in cubic Galileon theories interacting with an extra scalar field. We show that bouncing models are always plagued with gradient instabilities, while there are always ghosts in wormhole backgrounds. * While, in the cosmological context, the energy density of Galileons can indeed increase in time in a healthy way, constructing a complete bouncing or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…Hereafter, it was generalized with an additional scalar in ref. [34] or with the full Horndeski theory in ref. [35].…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, it was generalized with an additional scalar in ref. [34] or with the full Horndeski theory in ref. [35].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the effective field theory (EFT) of nonsingular cosmologies [8][9][10], this No-go result has been more clearly illustrated. It is found that the stable nonsingular cosmological models can be implemented only in the theories beyond cubic Galileon, (see also [11,12]). …”
Section: Introductionmentioning
confidence: 99%
“…If there is no gradient instability (B(t) > 0), the strict positivity of the function N (t) defined in Eq. (16) implies that the integral in the denominator of the expression for γ(t) in Eq. (15) is positive definite and increasing monotonically for all t > t 0 .…”
mentioning
confidence: 99%